Efficacy, Mechanism and Antiviral Resistance of Neuraminidase Inhibitors and Adamantane against Avian Influenza - Dyah Ayu Hewajuli; NLPI Dharmayanti (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2019)
Vaccination and antiviral drug are often used to control influenza. However, the effectiveness of vaccine was impaired due to the emergence of new variant of virus strain. Antiviral drug consists of prophylactic and curative substances, namely M2 ion channel inhibitors (adamantane; amantadine and rimantadine) and neuraminidase (NA) inhibitors (NAIs; oseltamivir, zanamivir, peramivir, laninamivir). The synthesis and modification of antiviral neuraminidase (NA) inhibitors (NAIs) and adamantanes increased the antiviral effectiveness. The mechanism of the neuraminidase inhibitor is to prevent influenza infection by inhibiting the release of the virus from internal cells. Adamantane is antiviral drug that selectively inhibits the flow of H+ ions through M2 protein to prevent the uncoating virus particles getting into the endosome. The substitution of (H275Y, S247N, I223L, K150N, R292K, I222T, R152K, R118K, E119V) on NA protein caused resistance of avian influenza virus against the neuraminidase inhibitor. The combination of mutations (S247N, I223L, K150N) increased the resistance of influenza A (H5N1) virus. The diffusion of adamantane resistance varies among HA subtypes, the species of host, the period of isolation, and region. Mutations at residues of 26, 27, 30, 31 or 34 transmembrane M2 protein caused adamantane resistance. The unique substitution (V27I) of M2 protein of clade 2.3.2 H5N1 subtype isolated in Indonesia in 2016 has been contributed to the amantadine resistance. Antiviral combination of M2 ion channel inhibitors and neuraminidase (NA) inhibitors is effective treatments for the resistance.